Identifying key priorities for research to protect the consumer with food hypersensitivity: A UK Food Standards Agency Priority Setting Exercise. Issue 10 (23rd July 2021) - Turner, Paul J.; Andoh‐Kesson, Elizabeth; Baker, Sarah; Baracaia, Alexa; Barfield, Alisha; Barnett, Julie; Brunas, Karen; Chan, Chun‐Han; Cochrane, Stella; Cowan, Katherine; Feeney, Mary; Flanagan, Simon; et al.
Abstract: Introduction: Food hypersensitivity (FHS), including food allergy, coeliac disease and food intolerance, is a major public health issue. The Food Standards Agency (FSA), an independent UK Government department working to protect public health and consumers' wider interests in food, sought to identify research priorities in the area of FHS. Methods: A priority setting exercise was undertaken, using a methodology adapted from the James Lind Alliance—the first such exercise with respect to food hypersensitivity. A UK‐wide public consultation was held to identify unanswered research questions. After excluding diagnostics, desensitization treatment and other questions which were out of scope for FSA or where FSA was already commissioning research, 15 indicative questions were identified and prioritized by a range of stakeholders, representing food businesses, patient groups, health care and academia, local authorities and the FSA. Results: 295 responses were received during the public consultation, which were categorized into 70 sub‐questions and used to define 15 key evidence uncertainties ('indicative questions') for prioritization. Using the JLA prioritization framework, this resulted in 10 priority uncertainties in evidence, from which 16 research questions were developed. These could be summarized under the following 5 themes: communication of allergens both within the food supply chain and then to the end consumer (ensuring trust in allergen communication); the impact of socio‐economic factors on consumers with FHS; drivers of severe reactions; mechanism(s) underlying loss of tolerance in FHS; and the risks posed by novel allergens/processing. Discussion: In this first research prioritization exercise for food allergy and FHS, key priorities identified to protect the food‐allergic public were strategies to help allergic consumers to make confident food choices, prevention of FHS and increasing understanding of socio‐economic impacts. Diagnosis and treatment of FHS was not considered in this prioritization.